The Application of Quantum Learning to Improve Self–Learning Motivation and Learning Outcomes of the 8th Grade Students of State Junior High School 2 Balerejo Madiun - Eni Windarti; Satrijo Budiwibowo; Moh. Rifa’i (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This study aims to determine the increase in self-learning motivation and learning outcomes in students of class VIII-B at State Junior High School 2 Balerejo Madiun Academic Year 2019/2020. To improve the ability of independent learning motivation and students' social studies learning outcomes, a class action research study was conducted consisting of two cycles. Each cycle consists of planning, implementing, observing and reflecting. The subjects of this study were students of class VIII-B at State Junior High School 2 Balerejo Madiun in Academic Year 2019/2020 consisting of 30 students. Data collection techniques used observation, questionnaires, tests and documentation. Result reveals that there are increasing motivation of students' independent learning in the first cycle obtained from average percentage of 59.8% (sufficient criteria) into 79.7% (high criteria). The average of student learning outcomes in the first cycle of 68.80 with a classical completeness of 57%. The average student learning outcomes in the second cycle amounted to 80.27 with a classical completeness of 87%. Based on the results of the study it can be concluded that the application of the Quantum Learning model increases motivation for independent learning and learning outcomes. The teachers should provide motivation or appreciation in the form of grades on student assignments, so students are motivated to learn because they feel valued. Quantum Learning models can be used as an alternative to varying learning models.